Pemanfaatan Aplikasi Perplexity AI pada Mata Pelajaran PAI di SMK Ciledug Al-Musaddadiyah - Evita Yuliatul Wahidah; Bung Harir Sulthonudin; Deba Muslim Abdullah (MASAGI : Jurnal Pendidikan Agama Islam, 2026)
Phase F (XI TKJ) at Musaddadiyah Vocational School has several students who are not yet aware of Perplexity AI as a technological tool to aid in the completion of assignments. The assignments from the PAI subject they receive mostly still consist of taking notes and working on Student Worksheets (LKS). As the digital era continues to develop, the utilization of technology, especially AI (Artificial Intelligence), becomes increasingly important in the field of education. Technology is something that can assist people around the world in daily activities, both in work and education. This research employs a descriptive qualitative approach. The qualitative approach is one of the important methods for understanding a social phenomenon and the individual perspectives of those being studied. The method used in this study is descriptive research method utilizing a qualitative approach. The data collection procedures used were interviews, observations, and documentation. The data sources used were primary data sources and secondary data sources. Meanwhile, the data analysis technique went through four stages, namely data collection, data reduction, data presentation, and conclusion drawing. The research results show that the use of the Perplexity AI application in the performance of student tasks in PAI subjects at SMK Ciledug Al-Musaddadiyah is very beneficial, not only in assisting independent tasks but also in enhancing knowledge, understanding, and the rapid search for information on various topics, although there are negative impacts associated with the Perplexity AI application. Keywords: Artificial Intelligence, Islamic Religious Education